2019
DOI: 10.1080/23793406.2019.1625283
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and breakthroughs: engaging in socially just ways towards issues of indigeneity, identity, and whiteness in teacher education

Abstract: The context for this study is set within the traditional country of the Yugarabul, Yuggera, and Jagera peoples. We acknowledge that they are the traditional custodians and appreciate their blessing to conduct our work and study upon their traditional lands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…Although Wolfe et al's 13 group had participated in professional development at a higher percentage (90%) than those in the present study (68%), both studies found staff actively seek and would appreciate further opportunities to build on these foundations. This is not always the case, however, as reported in other research where staff have resisted change 37,38 …”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Although Wolfe et al's 13 group had participated in professional development at a higher percentage (90%) than those in the present study (68%), both studies found staff actively seek and would appreciate further opportunities to build on these foundations. This is not always the case, however, as reported in other research where staff have resisted change 37,38 …”
Section: Discussionmentioning
confidence: 78%
“…This is not always the case, however, as reported in other research where staff have resisted change. 37,38 It is natural to expect that undergraduates who are about to enter the workforce would already be aware of the realities behind the government reports and statistics, yet data revealed students had multiple knowledge gaps and lack of experiential understanding. Indeed, many students initially identified with the first step of Well's 6 stage model, harbouring unconscious biases.…”
Section: Discussionmentioning
confidence: 99%
“…There should be also unconscious bias training for all staff in the school including headteachers, teachers, governors, as well as learning support and office staff. Such training and initiatives, as argued by researchers that looked into Whiteness, racism, ethnic diversity and education (see Farine-Wu et al, 2020 and Riley et al, 2019) will help White teachers to prepare to work in multicultural schools and to improve their knowledge on race and diversity while meeting the varying academic needs of ethnically diverse students. We also recommend more training that focus on exploration of systematic racial biases and explicit racial behaviours and how they manifested in organisations, training on white privilege that relates to the workforce, good practice training on race equality in education and training on understanding multicultural education and the importance of diversity and anti-racism and inclusive curriculum training for teachers and school leaders.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence from our study and elsewhere also makes a case for teachers training and educational programme to be more deliberate about preparing White British teachers for multicultural education and to teach students from all ethnic backgrounds. It is important that all teachers have access to robust and quality Continuing Professional Development (CPD) training to meet the educational needs of black students and understand the importance of race equality (Riley et al, 2019). There should be also unconscious bias training for all staff in the school including headteachers, teachers, governors, as well as learning support and office staff.…”
Section: Recommendations and Implications For Policy And Practicementioning
confidence: 99%
“…Most importantly, on our own, the biases we hold are less likely to be challenged or dismantled. Instead, developing collaborative networks, like professional learning communities, can increase capacity and reduce isolation for instructors while also increasing the longevity of important diversity initiatives (Allen‐Ramdial & Campbell, 2014 ; Bowne et al, 2011 ; Riley et al, 2019 ). Professional learning communities allow for the exchanging of ideas between teaching faculty and ensures that missteps in the early stages of anti‐racist and anti‐colonial work occurs alongside other instructors, and not in front of students before instructors have the tools to navigate those missteps in productive ways while teaching.…”
Section: A Framework For Collaborative Professional Learning Communit...mentioning
confidence: 99%